2019
DOI: 10.1103/physrevb.99.195120
|View full text |Cite
|
Sign up to set email alerts
|

Competing phases of interacting electrons on triangular lattices in moiré heterostructures

Abstract: We study the quantum many-body instabilities of interacting electrons with SU(2)×SU(2) symmetry in spin and orbital degrees of freedom on the triangular lattice near van-Hove filling. Our work is motivated by effective models for the flat bands in hexagonal moiré heterostructures like twisted bilayer boron nitride and trilayer graphene-boron nitride systems. We consider an extended Hubbard model including onsite Hubbard and Hund's couplings, as well as nearest-neighbor exchange interactions and analyze the dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 60 publications
3
53
0
Order By: Relevance
“…We close this paper with remarks about two solid-state platforms that would be described by similar KK models: the trilayer graphene/hexagonal boron nitrite heterostructures (TLG/hBN) [27][28][29][30] and the j = 3/2 compound α-ZrCl 3 [19]. KK models for TLG/hBN also display twofold orbital degeneracy, but these Wannier orbitals are located on a triangular lattice, which implies that our results are not extendable to this system.…”
Section: Discussionmentioning
confidence: 90%
“…We close this paper with remarks about two solid-state platforms that would be described by similar KK models: the trilayer graphene/hexagonal boron nitrite heterostructures (TLG/hBN) [27][28][29][30] and the j = 3/2 compound α-ZrCl 3 [19]. KK models for TLG/hBN also display twofold orbital degeneracy, but these Wannier orbitals are located on a triangular lattice, which implies that our results are not extendable to this system.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, previous studies have shown that the superfluid density of flat band systems is determined by the Chern number, quantum metric, or Berry curvature [17][18][19], despite the fact that effective mass of the electrons in a flat band is infinite. Recently, it has been proposed [20][21][22][23] that the observed superconductivity in twisted bilayer graphene [24,25] stems from quantum geometric properties of quasiflat Bloch bands.…”
mentioning
confidence: 99%
“…Whether these topological states can arise as the leading instability at the Van Hove doping becomes an interesting topic to explore. It has been shown that the imaginary charge density wave is degenerate with the real spin density wave with spin flavors N f = 2, and is further dominant universally at larger number of flavors N f ≥ 4 [28,30]. Meanwhile, the staggered currents have also been proposed in a π-flux triangular lattice [11], as well as in the doped chiral spin liquid [31].…”
Section: Introductionmentioning
confidence: 99%